Note on a Imperfectly Known Himalayan Bamboo Sinarundinaria Arunachalensis and Identity of Pleioblastus Simonii in Arunachal Hills - Naithani, H. B.; Kandwal, Manish K. (Indian Forester, 2014)
no abstract